Processos educativos estéticos não formais e memória étnica : o caso do Coral Municipal Alegria Franciscana - Federizzi, Roberta Bassani (2008)
This research belongs to the research line educative processes and language study and it has as main goals the organization of the historic of the Municipal Choir Alegria Franciscana, Marau-RS, and the deepening of the non-formal learning processes realized in this group. The problemsolving process involve the issues related to the educational esthetic processes, to the meaning of the musical language, the relevance of the use of the vêneto dialectic and the preservation of the ethnic memory between a group of adult men and women members of the choir above named. The study of qualitative ethnographic approach was established in the group during ten meetings, recorded during the rehearsals and the presentations, and also the use of interviews. The study concludes that, in a non formal space, where this choir lies, happens an educative process through the learning of folkloric songs the use of the vêneto dialect and the spreading of the Italian culture. Through the memories, bonds are put into effect, involving the group through feelings and also socially, truing, like that, to keep the Italian culture alive, emphasizing the Veneto one